Economic study of relationship between privatization and economic growth from a sample of developing countries - Al-Otaibi, Mohamed Meteb, author; Fan, Liang-Shing, advisor; Olienyk, John P., committee member; Fan, Chuen mei, committee member; Bernasek, Alexandra, committee member (Colorado State University. Libraries, 2006)
After three decades of privatization worldwide, has the transfer of state-owned enterprises (SOEs)'s ownership to the private sector been welfare improving? What lessons have we learned from this experience so far? And what are the possible implications of this economic policy and what is its impact on economic growth for the developing countries (DCs), in particular, Saudi Arabia, Kuwait, Bahrain, Egypt, Jordan, Iran, Turkey, Morocco, Pakistan, India, Indonesia, Malaysia, Venezuela, Mexico, and Argentina? These are the main questions addressed in this study. Economists have studied the role of the privatization policy in economic growth to determine what causes economic development. Some argue that privatization of SOE's has a positive impact on real variables such as GDP, while others have not found relationship between privatization programs and economic development. This study investigates the effect of privatization on economic growth in fifteen countries with developing economies by using a cross-section model (OLS estimation) and a cross section-time series model using panel data analyses including four panel types which are: None, Common, Fixed effect, and Random effect. The results of the OLS regression reveal that in case of Saudi Arabia, Kuwait, Bahrain, Jordan, Iran, Morocco, Pakistan, India, Indonesia, Malaysia, Venezuela, Mexico, and Argentina, privatization has had a significant impact on the GDP level which reflects the economic growth at a 5% significance level. While in cases of Egypt and Turkey, the results reveal that there is a negative relationship between privatization indicators and economic growth at a 5% significance level. The result of the four-panel tests reveal that privatization has a positive and a significant impact at a 5% significance level and this is consistent with study hypothesis that privatization has an impact on the productivity of all factors in the economy, and it leads to improving the investment climate in the developing countries. Hence, the foreign direct investment (FDI) will increase and the economic growth will improve. These results are consistent with the effect of the privatization policy on the economic growth of each country individually (OLS regression) except Egypt and Turkey. My analysis has significant implications for policy makers of these countries that have yet to undertake large-scale privatization programs, such as Egypt and Turkey. They will have to use the revenue of privatization efficiently, evaluating the companies' assets and decreasing corruption in privatizing the public sector. In addition, these countries should look carefully at the effect of other components on economic growth such factors need to be managed efficiently at the micro and macro level. The results also suggest that a privatization policy is a must, and that allocating government revenue from privatization efficiently is necessary in order to insure continuous positive impact on economic growth.
Keywords: government sponsored enterprises; models; policy making; studies; competition